2015
DOI: 10.1021/np500793g
|View full text |Cite
|
Sign up to set email alerts
|

Puupehenol, a Potent Antioxidant Antimicrobial Meroterpenoid from a Hawaiian Deep-Water Dactylospongia sp. Sponge

Abstract: From the organic extract of a deep-water Hawaiian sponge Dactylospongia sp., a new potent antioxidant and antimicrobial meroterpenoid, puupehenol (1), was isolated. The structure of 1 was determined using spectroscopic techniques ((1)H and (13)C NMR, MS, IR, UV, [α]D). The known compound puupehenone (2) was also isolated and suggested as a probable artifact of the isolation procedures. Complete unambiguous (1)H and (13)C NMR data are provided for compounds 1 and 2. Bioassays performed with 1 and 2 showed them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 23 publications
(41 reference statements)
0
50
0
1
Order By: Relevance
“…20). 191 The authors suggested that the well-known puupehenone may be a work-up artefact of the natural precursor puupehenol. Two epimeric sesquiterpene chromenols, named cyclorenierin A and B (158), were found in Haliclona sp., an Indo-Pacic sponge from Vanuatu.…”
Section: Spongesmentioning
confidence: 99%
See 1 more Smart Citation
“…20). 191 The authors suggested that the well-known puupehenone may be a work-up artefact of the natural precursor puupehenol. Two epimeric sesquiterpene chromenols, named cyclorenierin A and B (158), were found in Haliclona sp., an Indo-Pacic sponge from Vanuatu.…”
Section: Spongesmentioning
confidence: 99%
“…26). 227 Several low molecular weight chromenes, such as pterochromenes L1 (190), L2 (191) and L4 (192), were isolated from Taiwanese Pteris lingipinna 228 . 6-Hydroxyeupatoriochromene B (193) was obtained from Ageratina riparia (Asteraceae) 229 and nally, one of the rst insect anti-juvenile hormones, precocene 2 (194) (6,7-dimethoxy-2,2-dimethylchromene) was found in Ageratum houstonianum (Asteraceae).…”
Section: Plantsmentioning
confidence: 99%
“…Terpene quinones, including puupehenone metabolites, have been extensively studied for their antimicrobial and cytotoxic properties (32,(48)(49)(50)(51)(52). Nonetheless, this is the first report demonstrating that they selectively inhibit dormant drug-tolerant M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…The FRAP assay performed was slight modified according to the previous reported literature252627. The FRAP reagent was freshly prepared by adding 3 M CH 3 COOH buffer (pH 3.6), 0.1 M 2,4,6-Tris(2-pyridyl)-s-triazine and 0.2 M FeCl3 at 10:1:1 volume ratio in 0.4 M HCl.…”
Section: Methodsmentioning
confidence: 99%